Carbon neutral higher education institutions : a reality check, challenges and solutions - Ahonen, Veronica Lucia; Woszczek, Aleksandra; Baumeister, Stefan; Helimo, Ulla T.; Jackson, Anne Kristiina; Kopsakangas-Savolainen, Maria; Kääriä, Juha; Lehtonen, Tommi; Luoranen, MIka; Pongrácz, Eva; Soukka, Risto; Vainio, Veera; et al. (Emerald, 2024)
Purpose Calculating an organization's carbon footprint is crucial for assessing and implementing emission reductions. Although Finnish higher education institutions (HEIs) aim for carbon neutrality by 2030, limited research exists on plans to reach a similar target in any country. This paper aims to address the shared and individual challenges Finnish HEIs have with carbon footprint calculations, reductions, resources and offsetting. Design/methodology/approach A survey was targeted to sustainability experts in all 38 HEIs in Finland to identify key patterns and trends in the focus fields of the study. SWOT analysis was used to classify main strengths, opportunities, weaknesses and threats, based on which a series of policy recommendations was drafted. Findings Finnish HEIs are committed to carbon footprint tracking (97%, annually by 87%). The lack of standardization and the number of external stakeholders complicate accounting indirect emissions, impeding comparability and reliability. Only 39% had set separate emission reduction targets, suggesting a preference for carbon footprint over other environmental impact indicators. Insufficient monetary and human resources emerged in 23% of institutions, especially those smaller in size. Only 52% had clear offsetting plans, with shared concerns over trust and responsibility. Originality/value By including both research universities and universities of applied sciences, the findings provide an unprecedented outlook into the entire Finnish HEI sector. The policy recommendations guide HEIs both locally and globally on how to improve their transparency and scientific integrity, reflect on core successes and weaknesses and how they complete their objectives of education, research and social impact while promoting stronger sustainability.
Keywords: Carbon accounting; Corporate sustainability; Higher education institutions; Sustainability; carbon footprint; carbon neutrality